Development of an rpS6-Based Ex Vivo Assay for the Analysis of Neuronal Activity in Mouse and Human Olfactory Systems - Broillet-Olivier, Emma; Wenger, Yaëlle; Gilliand, Noah; Cadas, Hugues; Sabatasso, Sara; Broillet, Marie-Christine; Brechbühl, Julien (International journal of molecular sciences, 2024)
Olfactory sensitivity to odorant molecules is a complex biological function influenced by both endogenous factors, such as genetic background and physiological state, and exogenous factors, such as environmental conditions. In animals, this vital ability is mediated by olfactory sensory neurons (OSNs), which are distributed across several specialized olfactory subsystems depending on the species. Using the phosphorylation of the ribosomal protein S6 (rpS6) in OSNs following sensory stimulation, we developed an ex vivo assay allowing the simultaneous conditioning and odorant stimulation of different mouse olfactory subsystems, including the main olfactory epithelium, the vomeronasal organ, and the Grueneberg ganglion. This approach enabled us to observe odorant-induced neuronal activity within the different olfactory subsystems and to demonstrate the impact of environmental conditioning, such as temperature variations, on olfactory sensitivity, specifically in the Grueneberg ganglion. We further applied our rpS6-based assay to the human olfactory system and demonstrated its feasibility. Our findings show that analyzing rpS6 signal intensity is a robust and highly reproducible indicator of neuronal activity across various olfactory systems, while avoiding stress and some experimental limitations associated with in vivo exposure. The potential extension of this assay to other conditioning paradigms and olfactory systems, as well as its application to other animal species, including human olfactory diagnostics, is also discussed.
Keywords: čichové buňky; Smell; Ribosomal Protein S6; Phosphorylation; Humans; fosforylace; Odorants; lidé; zvířata; myši; myši inbrední C57BL; Olfactory Mucosa; Mice; odoranty; čich; Olfactory Receptor Neurons; Vomeronasal Organ; Male; ribozomální protein S6; Mice, Inbred C57BL; Animals; mužské pohlaví; vomeronazální orgán; čichová sliznice